2018
DOI: 10.3390/ijms19082199
|View full text |Cite
|
Sign up to set email alerts
|

Harmful Effects and Potential Benefits of Anti-Tumor Necrosis Factor (TNF)-α on the Liver

Abstract: Anti-tumor necrosis factor (TNF)-α agents represent an effective treatment for chronic inflammatory diseases. However, some concerns about their potentially undesirable effects on liver function have been reported. On the other hand, evidence of their therapeutic effects on certain liver diseases is accumulating. Many data showed the safety of anti-TNF-α in patients with chronic hepatitis B and C and in liver transplanted patients even if a strict follow-up and prophylaxis are recommended in well-defined subgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 144 publications
1
51
0
Order By: Relevance
“…Moreover, in accordance with our previous systematic review supporting a positive association between H pylori ‐I and homeostasis model assessment IR (HOMA‐IR), as index of IR, the individuals with H pylori ‐I had higher glucose, insulin, and HOMA‐IR compared to those without previous or current H pylori ‐I. Noteworthy, the former had also higher liver function tests (alanine transaminase [ALT] and aspartate transaminase [AST]) and tumor necrosis factor (TNF)‐α ; TNF‐α is considered a key pathogenetic cytokine for NAFLD, and experimental data appear to confirm that anti‐TNF‐α agents may be significant for NASH treatment . Of note, one study published previous to ours reported that H pylori ‐I was one of the independent risk factors for the development of NAFLD; however, due to language restriction, this study cannot be presented in detail.…”
Section: Clinical Studies On the Association Between Helicobacter Pylsupporting
confidence: 83%
See 1 more Smart Citation
“…Moreover, in accordance with our previous systematic review supporting a positive association between H pylori ‐I and homeostasis model assessment IR (HOMA‐IR), as index of IR, the individuals with H pylori ‐I had higher glucose, insulin, and HOMA‐IR compared to those without previous or current H pylori ‐I. Noteworthy, the former had also higher liver function tests (alanine transaminase [ALT] and aspartate transaminase [AST]) and tumor necrosis factor (TNF)‐α ; TNF‐α is considered a key pathogenetic cytokine for NAFLD, and experimental data appear to confirm that anti‐TNF‐α agents may be significant for NASH treatment . Of note, one study published previous to ours reported that H pylori ‐I was one of the independent risk factors for the development of NAFLD; however, due to language restriction, this study cannot be presented in detail.…”
Section: Clinical Studies On the Association Between Helicobacter Pylsupporting
confidence: 83%
“…[ALT] and aspartate transaminase [AST]) and tumor necrosis factor (TNF)-α 15 ; TNF-α is considered a key pathogenetic cytokine for NAFLD, and experimental data appear to confirm that anti-TNF-α agents may be significant for NASH treatment. 17 Of note, one study published previous to ours reported that H pylori-I was one of the independent risk factors for the development of NAFLD 18 ; however, due to language restriction, this study cannot be presented in detail.…”
mentioning
confidence: 79%
“…24 Furthermore, adalimumab, an anti-TNFa drug, has demonstrated efficacy in the treatment of HS 1 and several experimental data suggest that TNF-a blockade might be an important target to treat NASH. 25 Comparing the diagnosis of NAFLD in patients with HS and controls, we found that those with HS had a higher prevalence of obesity and metabolic syndrome, and interestingly, greater liver stiffness. It should be noted that smoking was a confounding factor since active smokers are more frequent in the HS group.…”
Section: Discussionmentioning
confidence: 84%
“…This common pathogenesis may explain, at least in a subset of patients, the development of NASH in the absence of classic metabolic risk factors . Furthermore, adalimumab, an anti‐TNFα drug, has demonstrated efficacy in the treatment of HS and several experimental data suggest that TNF‐α blockade might be an important target to treat NASH …”
Section: Discussionmentioning
confidence: 99%
“…Previous reports implied potential hepatotoxicity of anti-TNF-α agent, including idiosyncratic hepatic injury and autoimmune hepatitis. 36 In the rat models, previous experiments implied a pivot role of TNF-α in the pathogenesis of NASH. 11 Administration of infliximab could reverse diet-induced hepatic steatosis in rats.…”
Section: Discussionmentioning
confidence: 99%